A method of improving chatter-free conditions with combined-mode milling. (January 2016) - Ozoegwu, Chigbogu Godwin; Ofochebe, Sunday M.; Omenyi, Sam N.
Highlights: The core findings of this work are: A mode combining up- and down-milling is proposed for 3-axis machining. The combined mode stabilizes milling process under certain geometric conditions. Combined mode is of productive technological application in finish slotting. There is a potential for power savings from proposed technological application. Five-point procedure for making the most of dynamics of the combined mode is given. The procedure guarantees stable positioning of tool relative to any discontinuity. Abstract: An analytical foundation for proposing a new method of highly productive finish slotting with 3-axis end-milling is presented. This is done by considering process stability of combined-mode end-milling with a combination of both up-milling (conventional) and down-milling (climb) modes. Physically the combined mode occurs when a pre-existing slot exists in what could have been a full-immersion process. A novel geometric consideration is presented for complete definition of size and location of the pre-existing slot in terms of the component radial immersions of the combined mode. The sum of component radial immersions constitutes the effective radial immersion. It is seen that some combinations of size and location of the pre-existing slot could engender heightened stability which reflects as elevated stability lobes with hyper-productive lobbing effects. Procedure for arriving at the stabilizing combinations of size and location of the pre-existing slot is summarized in five steps in the conclusion. This procedure was followed in arriving at combinations that yielded very high MRR per active pass and very low finish-slotting time for a numerically studied system. Incorporation of the productive combinations in Computer Numerical Control (CNC) code for mass finish slotting in future industrial workshops implementing the proposed technology of multi-spindle system with an arrangement of pre-slotting tools stabilizing the finish-slotting tool is expected to considerably reduce of manufacturing time.